2005
DOI: 10.1007/s15010-005-4019-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Severe Sepsis in Intensive Care Units in the Slovak Republic

Abstract: We estimate 1,770 cases of severe sepsis hospitalized at Slovak adult intensive care units per year. Hospital mortality for severe sepsis remains very high (51.2%) and is associated with advanced age (over 50 years), number of failing organs and higher admission and maximum SOFA scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
4
18
0
3
Order By: Relevance
“…The serious conditions on ICU admission were associated with hindered availability of intensive care stations (which is less than 20 stations per 100 hospital beds in Poland). A similar situation was observed in Slovakia [6].…”
Section: Discussionsupporting
confidence: 82%
“…The serious conditions on ICU admission were associated with hindered availability of intensive care stations (which is less than 20 stations per 100 hospital beds in Poland). A similar situation was observed in Slovakia [6].…”
Section: Discussionsupporting
confidence: 82%
“…Until now, the only available results were those of the Slovak study by Zahorec et al from 2005, which monitored 121 patients with a reported mortality of 51.2% (ref. 25 ). The first descriptive data on epidemiology of sepsis/severe sepsis in patients in the Czech Republic was assembled in 2003 thanks to a prospective, multicenter, one-day observational questionnaire by Cerny et al, which included 327 patients from 53 ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…Median APACHE II score for all patients was 21 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Non-survivor patients had a median APACHE II score that was signifi cantly higher (27; …”
Section: Resultsmentioning
confidence: 99%
“…Among these 554 patients, we recorded sepsis in 30 (2.5%), severe sepsis in 269 (22.8%), and septic shock in 255 (21.6%) (Figure 1). The median APACHE II score was 13 (10-18) for patients without SIRS; 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) …”
Section: Resultsmentioning
confidence: 99%